A preliminary study on the relationships between diurnal melatonin secretion profile and sleep variables in patients emergently admitted to the coronary care unit. (July 2015) - Takaesu, Yoshikazu; Futenma, Kunihiro; Kobayashi, Mina; Komada, Yoko; Tanaka, Nobuhiro; Yamashina, Akira; Inoue, Yuichi
<x xml:space="preserve">Abstract</x> To clarify the significance of melatonin secretion under intensive care conditions, we investigated melatonin secretion profiles and sleep parameters of 23 patients just after admission to the coronary care unit (CCU) and 19 age-matched controls. Sleep parameters were evaluated by actigraphy, and melatonin secretion was assessed by measuring the urinary 6-sulphatoxy melatonin (6-SMT). 6-SMT secretion was lower and nocturnal sleep parameters were less satisfactory in the subjects than those in the controls, and there were positive correlations between these variables, particularly in the subject patients. The lowered melatonin secretion might be involved in the mechanism of insomnia in CCU patients.